Public Relations Strategis di Perbankan Syariah dan Lembaga Non-Bank: Membangun Kepercayaan dan Citra Melalui Komunikasi Efektif - Faizah, Nilna Alfa (Maliki Interdisciplinary Journal, 2025)
This article discusses the strategic role of public relations (PR) in strengthening the image and building public trust in Islamic banking and non-banking institutions. Drawing on various case studies and recent research, including digital PR strategies, influencer marketing, and integrated marketing communications approaches, the article highlights how Islamic institutions can optimize relationships with both Muslim and non-Muslim customers. Furthermore, the article explores PR adaptations during the Covid-19 pandemic and its implications for the reputation of Islamic financial institutions. The discussion provides practical recommendations for PR managers in implementing effective, transparent, and Sharia-compliant communication strategies to increase purchase intention and customer loyalty.